Cybercrime and Law Enforcement Challenges in the Era of Criminal Law Digitalization - Juhari; Sunarto; Zabidin (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The rapid advancement of information technology in the digital era has brought significant convenience to various aspects of human life, yet it has also given rise to new forms of criminal behavior known as cybercrime. This phenomenon encompasses a wide range of unlawful acts such as hacking, data theft, online fraud, and the dissemination of false information, all of which can cause serious social and economic harm. Such developments demand a legal system that can adapt to the dynamic, borderless, and often untraceable nature of cyberspace. This article aims to describe the various types of cybercrimes emerging in Indonesia, analyze the key challenges in law enforcement, and propose strategic measures to strengthen the effectiveness of their handling. The study employs a qualitative method with a normative juridical and descriptive-analytical approach through the examination of relevant literature, legal frameworks, and national research findings. The results indicate that law enforcement against cybercrime in Indonesia faces several obstacles, including regulatory gaps that fail to keep pace with technological progress, limited resources among law enforcement personnel, the complexity of digital evidence, and weak inter-agency and cross-border coordination. Therefore, it is essential to harmonize existing regulations, enhance the technical capacity of law enforcement officers, foster effective international cooperation, and promote public education on digital security to ensure that the national criminal justice system can respond comprehensively and adaptively to the challenges of digitalization.